Microbiological and Molecular Features Associated with Persistent and Relapsing Staphylococcus aureus Prosthetic Joint Infection - Irene Muñoz-Gallego; María Ángeles Meléndez-Carmona; Jaime Lora-Tamayo; Carlos Garrido-Allepuz; Fernando Chaves; Virginia Sebastián; Esther Viedma (MDPI AG, 2022)
Background: Persistent and relapsing prosthetic joint infection (PJI) due to Staphylococcus aureus presents a clinical challenge. This study aimed to provide an extensive description of phenotypic and genomic changes that could be related to persistence or relapse. Methods: Initial and second S. aureus isolates from 6 cases of persistent and relapsing PJI, along with clinical isolates from 8 cases, with favorable outcome were included. All isolates were studied by phenotypic and genotypic approaches. Results: Recurrent S. aureus isolates exhibited a significant increase in adhesive capacity, invasion and persistence compared to resolved isolates. No association was found for the presence or absence of certain genes with the persistence or relapse of PJI. All sequential isolates showed identical sequence type (ST). Resistance gene loss during the infection and a great diversity of variants in different virulence genes between the pair of strains, mainly in genes encoding adhesins such as fnbA, were observed. Conclusions: S. aureus-caused relapse and persistence PJI is associated with bacterial phenotypical and genotypical adaptation. The main paths of adaptation were persistence in the intracellular compartment, and the loss of antibiotic resistance genes and variant acquisition, especially in genes encoding adhesins.